Profile of an occupation – custom tailor - Schambeck, Arne [Verfasser] (My University, 2024)
"There is a training occupation separate from the fashion industry which combines creativity, dexterity, traditional craft skills and modern manufacturing processes. Custom tailors use their flair for design and fashion to produce everything from classic suits to theatrical costumes to one-off haute couture pieces for private persons and for the stage. This occupational profile sets out their most important tasks and provides training figures." (BIBB-Doku)
Keywords: S 6.2.2 Holzbearbeitung, Flechtwaren, Textil-, Leder- und Fellverarbeitung; 370; Maßschneider; Berufsbild; Berufsbeschreibung; Ausbildungsinhalt